A critique of teacher education practices in Trinidad and Tobago - Mark, Paula (School of Education, UWI, 1979)
This paper attempts to critically examine existing trends in teacher education programmes in Trinidad and Tobago, with a view to presenting specific guidelines for the improvement of the practice. It begins with a historical brief on the development of teacher education in Trinidad, followed by an examination of the desirability of the characteristics of existing programmes in the teachers' colleges
Paper presented at Staff Seminar, School of Education, UWI, St. Augustine
Keywords: Programme evaluation